Comparison of discrete cosine and wavelet transforms in RAW image compression systems - S.V. Sai; A.V. Zinkevich; E.S. Fomina (Компьютерная оптика, 2022)
The article describes features of digital processing of image signals in the process of coding based on discrete cosine (DCT) and wavelet transforms (DWT) that are used in the JPEG and JPEG2000 compression standards. To compare DCT and DWT, a digital model of the system has been developed that implements the same stages of signal processing, except for the stages of the proper discrete transforms. A method for analyzing the efficiency of the transformations based on objective assessments of image quality depending on the compression ratio is proposed. The peculiarities include the fact that, in contrast to the popular PSNR and SSIM metrics, it is proposed that the quality be assessed using the reduction factor for the RAW image format, the calculation of which is associated with the contrast sensitivity of vision. As a result of the research, quantitative estimates of the compression efficiency are obtained for the given quality parameters, depending on the type of conversion and the detail of the RAW images. Recommendations are made regarding the development of methods for increasing the efficiency of image compression based on DWT or DCT.